Design of Anchorage of CFRP Strips - Stepanek, Petr; Svarickova, Ivana (Communications - Scientific letters of the University of Zilina, 2002)
Anchorage of externally bonded reinforcement is the main problem for strengthening concrete structures with CFRP strips (Štěpánek & Šustalová 2000, 2001). This paper describes a form of the tests and some results implicating from different properties of anchorage elements. The test results are compared with values obtained from mathematical analysis of anchorage zones behavior and normal stress distribution along the anchorage length.